Alisher Navoi’s Philosophical Views (Texas Journal of Philology, Culture and History, 2026)
Alisher Navoi, recognized as one of the greatest poets, thinkers, and philosophers in the history of Central Asia, lived during the Timurid Renaissance, a period marked by cultural, intellectual, and artistic blossoming. His works, spanning poetry, prose, and treatises, manifest a profound engagement with metaphysical, ethical, and epistemological themes that place him among the seminal philosophers of the Islamic East. Navoi’s philosophical views, expressed through his literary masterpieces and treatises, reflect a synthesis of Islamic, Sufi, and Turkic traditions, infused with his remarkable originality, depth, and humanistic sensibility.